Social and Economic Impacts of Tourism Development on the Local Community of Kampung Pelangi, Semarang - Mendrofa, Herlinawati; Octafian, Ray (Pancasila International Journal of Applied Social Science, 2024)
The aim of this research is to explore and analyze the social and economic impacts of tourism development in Kampung Pelangi Semarang on the local community. The main research question to be answered in this study is: "How does tourism development in Kampung Pelangi Semarang affect the social and economic aspects of the local community?" This study will utilize a qualitative approach with data collection methods including in-depth interviews with residents of Kampung Pelangi, participant observation, and documentary studies. This is done to gain a deep understanding of the perspectives and experiences of the local community regarding the impacts of tourism development in their area. Local residents have also been able to capitalize on tourist needs by offering various local products and services, such as handicrafts and regional cuisine. Moreover, the increase in tourist numbers has brought about an increase in income for residents of Kampung Pelangi, both directly through the sale of goods and services, and indirectly through the growth of the local economy driven by tourism. Tourism development in Kampung Pelangi Semarang has had impacts on the social and economic lives of the community. New business opportunities, income growth, and changes in livelihoods are key factors driving economic welfare improvement for residents. Lifestyle changes, social interactions, and positive perceptions of tourism reflect the social impacts that have occurred. Efforts are needed to maintain a balance between tourism development and the preservation of local culture.